Nutrient values for harvested forages from northeastern Kansas - Marston, T.T.; Davis, Duane L.; Wood, Billy D.; Schaub, Rod (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forage testing is an important management tool available to cattle producers. Hay samples (n=42) from Shawnee, Douglas, and Osage counties of various forages (mostly alfalfa, brome hay, and prairie hay) recently were analyzed for nutrient composition. Results indicate that variability in crude protein and fiber (ADF and NDF) content exists. Alfalfa samples possessed crude protein content greater than reported values, whereas prairie samples were close to National Research Council reported values. In contrast, brome hay samples often had less crude protein than their NRC book values. Single samples of other forage types revealed that nutrient profiles of alternative forages could be successfully integrated into cattle feeding programs. These results strongly support the continued need for producers to practice forage sampling to optimize cattle feeding costs.
Keywords: Beef; Nutrient values; NE Kansas